Ball Collecting Robot - wala Hamad; Khayrieh Homran (My University, 2016)
Our Project is a smart ball collecting robot that analyzes its surrounding, detects existing ball objects and collects them to specific known point.   Ball Collector robot consists of two parts; the first part is image-processing, which is responsible for the analysis of input image and detecting existing balls using Raspberry Pi board   and Raspberry Camera. The second part is controlling robot movement and collecting balls process using Arduino Uno Microcontroller.   Our Robotic has many useful usages, for example, it can be used to help Tennis and Golf players to collect balls while they are training or playing matches.   Project developing flow started with configuring Raspberry Pi kit, installing operating system, configuring python and OpenCV in operating system. After that, we started writing ball tracking algorithm using OpenCV image processing library. After that, we started configuring our robotic car and hardware sensors and writing Arduino code to control car operation. Finally we connected Raspberry Pi code to Arduino and tested our ball collector operation.   We faced many problems during the development process. One of these problems is that Raspberry Pi is unreliable kit. Another problem is building robotic car with stable movement, many robotic cars does not move in stable straight line.   We ended up with ball collecting robotic car that collect balls from surrounding area to specific point.

.. .     .      . . . . .    configuring Raspberry Pi kit python and openCV   openCV . . . .
Ball Collecting Robot